f(x) = x − 6, g(x) = x^{2}

^{} Find the domain of (f + g)(x).

Find (f − g)(x).

Find the domain of (f − g)(x)

Find (fg)(x).

Find the domain of (fg)(x)

Find

Find the domain of

f(x) =(x-6)

g(x) = x^{2}

(f+g)(x) = (x-6) + x^{2}

domain = { x | x is real }

(f-g)(x) = (x-6) - x^{2}

(fg)(x) = (x-6) * x^{2} = x^{2} (x-6)

(f/g) (x) = (x-6)/ x^{2}

domain = { x | x is real and x ≠ 0 }

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up